`y = (3x - 4)(x^3 + 5)` Use the Product Rule to find the derivative of the function.

Textbook Question

Chapter 2, 2.3 - Problem 2 - Calculus of a Single Variable (10th Edition, Ron Larson).
See all solutions for this textbook.

1 Answer | Add Yours

hkj1385's profile pic

hkj1385 | (Level 1) Assistant Educator

Posted on

`y = (3x-4)*(x^3 + 5)`

`y' = 3(x^2)*(3x-4) + 3(x^3 + 5)`

`or, y' = 9x^3 - 12x^2 + 3x^3 + 15`

`or, y' = 12x^3 - 12x^2 + 15`

`or, y' = 3[4x^3 - 4x^2 + 5]`

``

We’ve answered 318,968 questions. We can answer yours, too.

Ask a question